Long-term study of indomethacin and alclofenac in treatment of rheumatoid arthritis. Issue 5961 (5th April 1975) - Aylward, M; Parker, R J; Holly, F; Maddock, J; Davies, D B
Abstract : Indomethacin and alclofenac were compared for 13 months under double-blind conditions in 109 patients with active, classical, or definite rheumatoid arthritis at a relatively early stage of the disease. Both indomethacin and alclofenac were clearly effective: most patients either improved or remained as well controlled as on entry. Alclofenac proved the more effective drug, however, producing a significantly greater reduction in morning stiffness, articular index, and erythrocyte sedimentation rate, and only in the alclofenac-treated group did functional capacity improve and latex-agglutination titres diminish. Comprehensive laborabory tests showed no significant deviation from normal which could have been attributed to either drug.